Islamization of research in history: a critical analysis - Ahsan, Abdullahil (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
History is the storehouse of knowledge and students of history must know how and why this knowledge is stored. Many sophistic authors have manipulated information about the human past in order to serve their selfcentered motivation. A critical evaluation and a rational assessment of such manipulation may be recognised as Islamization of Knowledge. In modern times, the perception of man has made significant impact in history writing. This article critically evaluates the manipulation of history by some historians and then examines how Darwinian and Freudian “scientific” perceptions have impacted history writings. There is a dire need to challenge such views by rational historians.